2002
DOI: 10.1128/mcb.22.14.5203-5211.2002
|View full text |Cite
|
Sign up to set email alerts
|

Novel Transcription Coactivator Complex Containing Activating Signal Cointegrator 1

Abstract: Human activating signal cointegrator 1 (hASC-1) was originally isolated as a transcriptional coactivator of nuclear receptors. Here we report that ASC-1 exists as a steady-state complex associated with three polypeptides, P200, P100, and P50, in HeLa nuclei; stimulates transactivation by serum response factor (SRF), activating protein 1 (AP-1), and nuclear factor B (NF-B) through direct binding to SRF, c-Jun, p50, and p65; and relieves the previously described transrepression between nuclear receptors and eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 28 publications
2
101
2
4
Order By: Relevance
“…The asc-1 gene (Y53F4B.15), a homolog of human activating signal cointegrator-1 (Jung et al, 2002), showed an average 28-fold increase in tags (p < 0.001). The non-coding transcribed telomeric sequence (tts-1) transcript (F09E10.11, reported in Jones et al, 2001) was also found at higher levels (average 57 fold increase) in both daf-2 adults and dauer larvae (p < 0.001).…”
Section: Correlation Of the Sage Data With Differences In Longevitymentioning
confidence: 99%
“…The asc-1 gene (Y53F4B.15), a homolog of human activating signal cointegrator-1 (Jung et al, 2002), showed an average 28-fold increase in tags (p < 0.001). The non-coding transcribed telomeric sequence (tts-1) transcript (F09E10.11, reported in Jones et al, 2001) was also found at higher levels (average 57 fold increase) in both daf-2 adults and dauer larvae (p < 0.001).…”
Section: Correlation Of the Sage Data With Differences In Longevitymentioning
confidence: 99%
“…Trip4, also called activating signal cointegrator 1 (Asc1), is a transcription coactivator of nuclear receptors that plays a pivotal role in the transactivation of NFB and AP1 (44). Trip4 also regulates androgen receptor transactivation and testicular function (45,46).…”
Section: Snail1 Induces Il-17 Expression To Inhibit Adipogenesismentioning
confidence: 99%
“…Nowadays, ASCC1 protein is considered to establish a cross talk with Jun and NF-kB that links inflammatory to tumor suppressive/oncogenic pathways (18). However, very little is known about ASCC1 function and its role in the NF-kB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TRIP4 contains a transactivation domain with a putative zinc finger motif, which serves as a binding site for TATA-binding protein, TFIIA, SRC1, CBP/p300, and nuclear receptors (19). It also interacts with a wide range of transcription factors including serum response factor, NF-kB, and AP1, and has been shown to be part of a coactivator complex that links these factors to the transcriptional machinery (18). Overexpressed TRIP4 has been normally local- ized in the nucleus but accumulates in the cytoplasm under serumdeprived conditions (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation